Aligning English with Design Practice: An ESP Needs Analysis for VCD Graphic Design Students - Ainayya Nabilla; Nur Hidayanto Pancoro Setyo Putro (Universitas Muhammadiyah Jember, 2026)
ESP learning materials needed to teach for specific programs like VCD-graphic design to prepare the students in the work demands. However, the general English still applied in the specific program without considering students’ needs. This study aimed to identify the target and learning needs of tenth grade graphic design students in the VCD program. The participants consisted of 33 students and an English teacher in VCD-graphic design program selected through purposive sampling. This study was a mix-method research design where the data were collected through questionnaire and interview. The collected data analyzed by using descriptive statistics and thematic analysis. This study revealed target needs of tenth grade students in VCD-graphic design programs requiring English skills that were closely related to the workplace demands in the VCD-graphic design program. As well as target needs, the students showed their interest in the procedures-related design which aligned with the program. Therefore, the English teacher expected to develop relevant learning materials to address students’ needs. However, this study had several limitations, for instance limited number of participants and only focused on the students’ and teacher’s preferences rather than observations. Therefore, the future studies are recommended to have large participants and observe the classroom implementations.